Efficacy of Alpha Lipoic Acid Supplementation in Sperm Parameters: A Systematic Review and Meta-Analysis of Randomized Trials - Iago Zang Pires; Marília Oberto da Silva Gobbo; Renan Yuji Ura Sudo; Tanize Louize Milbradt; Nilson Marquardt Filho; Gustavo Franco Carvalhal; Carlos Teodosio Da Ros (International Brazilian Journal of Urology, 2025)
ABSTRACT Introduction: Male factors contribute to 30 to 50% of infertility in couples. Treatment options for male infertility are limited, so antioxidant supplementation for idiopathic male infertility is currently being studied. Alpha lipoic acid (ALA) has a high antioxidant capacity and the potential to penetrate tissues, cells, and organelles, including mitochondria, due to its water and lipid solubility properties. The recent inclusion of randomized trials in the literature has required a new systematic review and meta-analysis to evaluate the efficacy of alpha lipoic acid in sperm parameter changes. Purpose: We aimed to perform a systematic review and meta-analysis of the currently available randomized trials comparing the effects of ALA supplementation versus placebo on sperm function in infertile male patients. Material and Methods: Pubmed, Embase, Cochrane Library, and Scopus databases were searched from inception to June 2024. A random-effects model was employed to compute mean differences and risk ratios for continuous and binary endpoints. Heterogeneity was evaluated through the prediction interval. A sensitivity analysis was conducted by systematically excluding one study at a time and recalculating the pooled effect. All statistical analysis was conducted using R software 4.4.1. The certainty of evidence was evaluated with the GRADE approach. Results were reported following the PRISMA statement guidelines. This study was registered in PROSPERO. Results: Five randomized trials comprising 250 patients with a mean age of 28 to 40 years were included in this analysis. Over a mean follow-up time of 3 months, ALA was associated with a reduced proportion of abnormal sperm morphology (MD −0.89; 95% CI −1.48 to −0.29; p=0.003), increased total motility (MD 13.49; 95% CI 3.52 to 23.46; p=0.008), and increased sperm progressive motility (MD 12.43; 95% CI 2.89 to 21.97; p=0.01). Additionally, ALA was associated with a higher pregnancy rate in two individual studies reporting the outcome, however, no significance was found in our pooled analysis (RR 2.28; 95% CI 0.66 to 7.85; p=0.1). Finally, ALA did not change ejaculation volume (MD 0.14; 95% CI −0.54 to 0.83; p=0.6), sperm concentration (MD 11.99; 95% CI −0.67 to 24.66; p=0.06), live sperm (MD 4.42; 95% CI −3.17 to 12.02; p=0.2), or total antioxidant capacity (MD 0.43; 95% CI −0.02 to 0.87; p=0.06). No adverse events were reported. Conclusion: In this meta-analysis, ALA was associated with a favorable change in sperm quality. However, there were no effects on pregnancy rates. ALA should be considered for patients with idiopathic infertility.